SCREENING OF EXTRACTION METHOD FOR ALKALOID ENRICHMENT OF PEPEROMIA PELLUCIDA (L.) KUNTH - Ahmad, Islamudin; Rissyelly, Rissyelly; Kurniawan, Agus; Munim, Abdul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aims of this study were to investigate the effect of extraction method modification of Peperomia pellucida (L.) Kunth herbs for alkaloid enrichment and thin layer chromatography (TLC) profile. Methods: The dried herbs were extracted with six different methods (including; method A, B, C, D, and E). The obtained extract solution was evaporated and was analyzed. Alkaloid content identified using Dragendorff spray reagent. The gravimetric method was used to determine of total alkaloid, and TLC profile was analyzed using a densitometer at a wavelength of 254 nm and 366 nm. Results: The results showed a difference from all modification of extraction method for alkaloid enrichment and their TLC profile. The use of eluent dichloromethane (DCM):methanol (95:5) was potential for isolation of the compound. From whole extraction methods, only one that tested positive for alkaloids was method A. Total alkaloids in DCM fraction amounted to 29.59 mg/g piperine. Conclusion: Based on the above results, method A can be applied for isolation of alkaloid compound from this herb.